Does Family Business Group Affiliation In Real Sector Firms Really Affect Their Performance? - Isik, Ozcan (Advances in Social Sciences Research Journal, 2017)
In this study, we empirically examine the performance effect of group affiliation by comparing the performance of firms that belong to family business groups with the performance of independent firms. For this purpose, we use a sample of 193 Turkish firms (i.e. 90 group affiliated firms and 103 non-group firms) quoted on the Istanbul Stock Exchange (Borsa Istanbul) during the 2005-2012 period. Based on ROA and Tobin’s Q performance measures, the findings obtained from the FEVD estimator reveal that group membership does not always positively affect the financial performance of member firms. There exists a threshold effect of group affiliation, i.e. big group firms are better performers than both small group firms and stand-alone firms. Furthermore, when taken into account of firms’ age, we find that positive effect of group affiliation is only valid for old group affiliated firms.